(untitled) (Research, Society and Development, 2024)
Introduction: The consumption of alcohol and electronic cigarettes has increased, raising concerns. Although electronic cigarettes have been promoted as a less harmful alternative to tobacco, questions about the associated risks have already been described in the literature. In addition, alcohol use is often linked to the need for socialization and stress management. Objective: To analyze the scientific evidence associated with the consumption of alcohol and electronic cigarettes by medical students. Methodology: Integrative review of the literature on alcohol and electronic cigarette consumption among medical students. Ten articles were selected and analyzed from the PubMed database. They were chosen based on criteria of relevance, methodological quality and diversity of samples. Results and Discussion: The analysis of the studies reveals that the use of electronic cigarettes among medical students is driven by the search for a modern image and socialization. The lack of awareness about the risks associated with vaping is worrying. Alcohol consumption is alarmingly prevalent among these students. The combination of electronic cigarette and alcohol use increases the risks to physical and mental health. Students turn to alcohol and e-cigarettes as ways to cope with stress, creating a cycle of addictive behavior. Conclusion: The use of these substances is a worrying problem, affecting physical and mental health. The lack of awareness about the risks of vaping and alcohol consumption related to academic stress requires attention. Awareness campaigns and interventions are needed to promote student well-being and help them face challenges in a healthier way.